Dynamics of phosphorus fractions in soils treated with dairy manure - Braos, L. B. [UNESP]; Bettiol, A. C.T. [UNESP]; Di Santo, L. G. [UNESP]; Ferreira, M. E. [UNESP]; Cruz, M. C.P. [UNESP] (My University, 2020)
The evaluation of phosphorus (P) transformations in soil after application of manure or mineral P can improve soil management and optimise P use by plants. The objectives of the present study were to assess organic and inorganic P forms in two soils treated with dairy manure and triple superphosphate and to establish relationships between soil P fraction levels and P availability. Soil organic and inorganic P fractions were quantified using a pot experiment with two soils, a typical Hapludox and an arenic Hapludult, with three types of fertiliser treatments applied (no fertiliser application, application of dairy manure, and application of triple superphosphate, by adding 100 mg P dm-3 in the form of fertiliser in the two latter treatments) and four incubation times (15, 45, 90, and 180 days). Inorganic P was fractionated into aluminium-bound, iron-bound, occluded, and calcium-bound P. Organic P was extracted sequentially using sodium bicarbonate, hydrochloric acid, microbial biomass, sodium hydroxide, and residual organic P. After incubation, maize plants were cropped to quantify dry matter yield and absorbed P. Application of dairy manure resulted in a significant increase in most of the organic P fractions, and application of triple superphosphate led to a significant increase in inorganic P fractions. Both fertilisers raised labile organic P fractions in the two soils. The major sinks of P in Hapludox were occluded and fulvic acid-associated P. In contrast, the major sink of P in Hapludult was iron-bound P. The available P levels were stable after application of dairy manure, and decreased with time when fertilised with triple superphosphate. In the Hapludox, the organic P fractions had a significant positive correlation with P uptake by plants. The results suggest that organic P mineralisation plays a more significant role in plant P uptake in the Hapludox soil and inorganic P forms are the main contributors to plant P uptake in the Hapludult soil.
Keywords: nuclear magnetic resonance; organic fertiliser; phosphorus availability; phosphorus pools